Analysis of the Effect of Enforcement of the Coal Export Ban on the Performance of Foreign Ship Agencies at PT Serasi Shipping Indonesia - Henry; April Gunawan Malau; Edy Kurniawan; Marlin S (Greenation International Journal of Economics and Accounting, 2023)
January 1 to 31, 2022 for holders of Mining Business Permits (IUP) or (IUPK) for the production operation stage, a ban on coal exports is enforced to ensure the fulfillment of domestic supply, namely coal for steam power plants, supply shortages have an impact on users. More than 10 million customers of PT PLN (Persero), ranging from the general public to the public, in the regions of Java, Madura, Bali, (jamali) and non-jamali, as well as causing a decline in the performance of the foreign ship agency run by PT Serasi Shipping Indonesia. Statistical analysis of the data in this study used the SPSS (Statistical Product and Service Solution) version 25 method used to perform statistical calculations using a computer. The data analysis techniques used in this study were Correlation Coefficient Analysis, Simple Linear Regression Analysis, Coefficient of Determination Analysis, Hypothesis Testing. Then based on the table above on X against Y, namely the Sig values ??of 0.000 0.005 and 6.554 2.467 It can be concluded that the implementation of the ban on coal exports has a significant positive effect on agency performance, so the hypothesis states that the implementation of the ban on coal exports has a positive effect on agency performance of foreign ships significant, or in conclusion the hypothesis is accepted. The implementation of the ban on coal exports has proven to have a positive and significant effect on the performance of foreign ship agencies at PT Serasi Shipping Indonesia with a regression coefficient with a value of 0.633 and a t-count value of 6.554 greater than a t-table value of 2.467 while the most dominant dimension for variable (X) is the decision to implement a ban with an average value (4.67) which is reflected by the indicator. variable (Y) is a service procedure with an average value (4.82) with the indicator Prohibition of coal exports applies to all coal mining entrepreneurs who have pocketed a mining business permit (IUP) or a special mining business permit (IUPK) with an average value (4.83). The implementation of the ban on coal exports has been shown to have a positive and significant relationship to the performance of foreign ship agencies at PT Serasi Shipping Indonesia as evidenced by a correlation coefficient with a value of 0.778 or 77.8% so that a strong correlation can be stated, while the remaining 0.222 or 22.2% caused by other factors outside of the research conducted.